2021
DOI: 10.1007/s42452-021-04724-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterizations of (Mg, Co, Ni, Cu, Zn)O high-entropy oxides

Abstract: High-temperature structural ceramic materials require stability in terms of thermal and mechanical properties. High entropy oxides (HEOs) are among the emerging novel family of advanced ceramic materials with peculiar functional properties. However, their thermal stabilities and mechanical properties are not well investigated. In this work, HEO systems were synthesized from binary oxides of MgO, CoO, NiO, CuO, and ZnO using solid-state reaction method at high temperature, after obtaining the individual oxides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…With the sintering temperature ranging from 850 to 1000 1C, the mixture of rock-salt and tenorite can be transformed into a single rock-salt phase. Desissa 54 and other research groups 23,[55][56][57][58][59][60] have also observed the same experimental phenomenon, demonstrating the high reversibility of (MgCoNi-CuZn)O. The cooling rate is also a factor in obtaining a single rock-salt structure (MgCoNiCuZn)O apart from sintered temperature.…”
Section: Temperature Controlsupporting
confidence: 57%
“…With the sintering temperature ranging from 850 to 1000 1C, the mixture of rock-salt and tenorite can be transformed into a single rock-salt phase. Desissa 54 and other research groups 23,[55][56][57][58][59][60] have also observed the same experimental phenomenon, demonstrating the high reversibility of (MgCoNi-CuZn)O. The cooling rate is also a factor in obtaining a single rock-salt structure (MgCoNiCuZn)O apart from sintered temperature.…”
Section: Temperature Controlsupporting
confidence: 57%
“…When elements are in equiatomic proportions, S config reaches the maximum. S config ≥ 1.5 R is recommended as “high entropy” system, 1.5 R > S config > 1 R is a “medium entropy” system, S config < 1 R is regarded as “low entropy” system . For HEOs, the dedication of anion sites has little effect on the S config since there is only one anion; that is, the role of oxygen vacancy is neglected.…”
Section: Introductionmentioning
confidence: 99%